Women and agricultural water resource management: A pathway towards obtaining gender equality - Ndey-Isatou Njie; Tacko Ndiaye (UN Chronicle, 2013)
Women are important stakeholders in agriculture water management—they play a key role in water and land conservation, rainwater harvesting, and watershed management. The Food and Agriculture Organization of the United Nations (FAO) estimates that 925 million people are undernourished and food production would have to increase by 70 per cent to feed a population of 9 billion people by 2050. Of the 1.5 billion hectares of cropland worldwide, a mere 277 million hectares is irrigated land, with the remaining 82 per cent being rain-fed land. Women play an important role in both irrigated and non-irrigated agriculture, and a larger number of women than men are engaged in rain-fed agriculture producing two thirds of the food in most developing countries. According to the latest FAO estimates, women account for an average of 43 per cent of the agricultural labour force in developing countries but in spite of this, water policies related to agriculture continue to wrongly assume that farmers are men, thus marginalizing women in water resource management.